Weak and strong convergence theorems of new iterations with errors for nonexpansive nonself-mappings - Somsak Thianwan (2018)
In this paper, a new three-step iterative scheme for nonexpansive nonself- mappings in Banach spaces is defined, and weak and strong convergence theorems are established for the new iterative scheme in a uniformly convex Banach space.